The impact of firm performance on executive compensation of publicly-listed companies in the Philippines - Azucena, Claire Anne D. (Animo Repository, 2016)
Having one of the highest and the most vital roles in a company, the executives need a constant source of motivation for them to execute well the roles assigned to them which will eventually have an effect with the firm's overall performance. The compensation committee will then evaluate the executives and will provide compensation which may or may not be appropriate depending on the actions and the performance of the executive for the period. This thesis investigates the effects of the variables of firm performance such as Tobin's Q, total stock return, return on assets, and earnings per share, to executive compensation. Data was gathered from the Philippine Stock Exchange (PSE), Securities and Exchange Commission (SEC), Osiris database, and related party disclosures, among others. The collected data was used conduct an analytical research and the results are presented on an aggregated basis and per industry. This study used panel data regression for it would require multiple cases of both financial information and nonfinancial information over a three-year period. Since panel data analysis includes three models, several tests were also used to determine which panel data regression model better captured the hidden heterogeneity. Based from the effects of the firm performance measures to executive compensation, this study implies that there is a weak link of pay-performance in Philippine companies used in this study. While earnings per share was shown to have a significant positive effect, return on assets did not have any significant effect. Furthermore, total stock return and Tobin Q have significant effects on different industries but not in aggregate.